TANGGUNG JAWAB PEMERINTAH UNTUK MEMBERIKAN PENDIDIKAN KEPADA ANAK TERLANTAR DALAM PERSPEKTIF UNDANG-UNDANG PERLINDUNGAN ANAK - Sheilla Chairunnisyah Sirait (DE LEGA LATA: JURNAL ILMU HUKUM, 2017)
Education for children is an absolute necessity that must be fulfilled throughout their life, without it, it is impossible for them to live in ideals desirable candidates for the next generation of the nation. Education is the most important means for the future and the future of the nation and state, so the responsibility of the government to children education should be a duty that is applied by providing all the basic needs of schools, the provision of facilities and infrastructure, professional teachers, and without Policies that are discriminatory toward students.